BLAMING THE VICTIM : OBJEKTIFIKASI KORBAN KEKERASAN SEKSUAL DALAM PEMBERITAAN DI MEDIA ONLINE BALAIRUNGPRESS.COM - Faatihah Dhuha Najib; Sunarto . (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Textual in this news is very interesting to study because it intersects with feminism as well as discussing controversy in the representation of victims, the purpose of this study is to find out the audience's meaning to the news